Femoral rotation unpredictably affects radiographic anatomical lateral distal femoral angle measurements - Miles, James E. (Veterinary and Comparative Orthopaedics and Traumatology, 2016)
Objective: To describe the effects of internal and external femoral rotation on radiographic measurements of the anatomical lateral distal femoral angle (a-LDFA) using two methods for defining the anatomical proximal femoral axis (a-PFA).Methods: Digital radiographs were obtained of 14 right femora at five degree intervals from 10° external rotation to 10° internal rotation. Using freely available software, a-LDFA measurements were made using two different a-PFA by a single observer on one occasion.Results: Mean a-LDFA was significantly greater at 10° external rotation than at any other rotation. The response of individual femora to rotation was unpredictable, although fairly stable within ±5° of zero rotation. Mean a-LDFA for the two a-PFA methods differed by 1.5°, but were otherwise similarly affected by femoral rotation.Clinical significance: If zero femoral elevation can be achieved for radiography, a-LDFA measurements do not vary much with mild femoral rotation (±5°). Outside of this range, a-LDFA varies unpredictably with femoral rotation.
Keywords: Femur; varus; radiography; canine